Regularities of pedagogical technique in a work of vocational training school teacher - Vovkovins’kyi, Mykola (Professional Pedagogics, 2012)
The problem concerning regularities of pedagogical technique of a vocational training school teacher is considered. The author shows that it is important to comply with the regularities in the course of pedagogi- cal activity.